West Nile fever as a relevant health hazard: The history of studying measures of and its prevention in Russia - A.V. Toporkov; E.V. Putintseva; S.K. Udovichenko (Analiz Riska Zdorovʹû, 2023)
The review generalizes data on West Nile fever manifestations in Russian between 1963 and 2022. Researchers have deter-mined peculiarities of the endemic process typical for this arboviral infection: cyclic rises in incidence with an interval of 1 to 8 years; the disease cases being predominantly registered in the south of the European part of the country; elevated risks of the disease for people aged 60 years and older; most West Nile fever cases without affecting the central nervous system with a continuous steady increase in the share of neuroinvasive forms. There are ongoing discussions of a considerable growth in an area where West Nile fever spreads as the incidence of the disease has been registered in Central Russia and this calls for assessment studies aimed at determining the northern borders of the infection area. The reviewed studies also systematize data on the WNV carriers and vectors and highlight the necessity to conduct large-scale experimental studies with their focus on examining susceptibility of various species of vertebrates and arthropods to the West Nile virus and assessing the efficiency of its transmission. The West Nile virus population that circulates in Russia has been shown to be heterogeneous and represented by the genotypes 1, 2, and 4, of which the genotype 2 is prevailing at present. The review also provides the findings of our own research with its focus on the genomes of the West Nile virus isolates indicating circulation of various genetic variants of the pathogen belonging to the genotype 2. The reviewed studies consider issues related to establishing epidemiological surveillance and sanitary-anti-epidemic (preventive) measures regarding West Nile fever in Russia and the principles of their organization at the present stage.